Molecular Chaperones as Prognostic Markers of Neuroblastoma - Liao, Yung-Feng; Hsu, Wen-Ming; Lee, Hsinyu; Hu, Ming-Kuan; Juan, Hsueh-Fen; Huang, Min-Chuan; Chang, Hsiu-Hao; Wang, Bo-Jeng; Shih, Yu-Yin; Tsay, Yeou-Guang (IntechOpen, 2012)
None